1999
DOI: 10.1111/1467-8527.00117
|View full text |Cite
|
Sign up to set email alerts
|

Standards and Professional Practice: The TTA and Initial Teacher Training

Abstract: This article examines the implications of the change from competences to standards for initial teacher training. It analyses the implicit interpretation of quality and standards of practice in Teacher Training Agency (TTA) documentation and compares it to that of the Management Charter Initiative in their new management standards. The TTA approach is challenged as incomplete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
7

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 10 publications
0
15
0
7
Order By: Relevance
“…The 2002 revised model, encompassing broader 'professional values and practice' (Training and Development Agency (TDA), 2002), was broadly welcomed as recognizing the wider professional context of teachers' work (Reynolds 1999). …”
Section: Introductionmentioning
confidence: 99%
“…The 2002 revised model, encompassing broader 'professional values and practice' (Training and Development Agency (TDA), 2002), was broadly welcomed as recognizing the wider professional context of teachers' work (Reynolds 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed the re-framing of initial teacher education as initial teacher training suggested that teacher knowledge was technical and finite rather than context-specific and open to critique. The definitive view of teaching represented by these Standards was reinforced by a lack of theoretical underpinning (Reynolds, 1999). Mahony and Hextall (2000) raised concerns about this missing rationale and argued that, in failing to provide any theoretical justification or acknowledge sources, the Standards mystified the values inherent within them.…”
Section: The Ite Curriculummentioning
confidence: 99%
“…Mahony and Hextall (2000) raised concerns about this missing rationale and argued that, in failing to provide any theoretical justification or acknowledge sources, the Standards mystified the values inherent within them. Prescriptive in relation to the kinds of strategies that student teachers should be taught, the first version of the Standards was criticized as overly technicist and lacking in any reference to the importance of professional judgements, professional values or effective relationships with colleagues and pupils (Reynolds, 1999).…”
Section: The Ite Curriculummentioning
confidence: 99%
“…In teacher education and in nurse education there has been a shift away from the competence model (Reynolds, 1999). Medical and legal education are not competence based.…”
Section: Implications For Social Workmentioning
confidence: 99%